2008
DOI: 10.1074/jbc.m803547200
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Aurora-A as a Direct Target of E2F3 during G2/M Cell Cycle Progression

Abstract: . Further, E2F3 directly binds to Aurora-A promoter and stimulates the promoter activity. Deletion and mutation analyses of the Aurora-A promoter revealed that a region located 96-bp upstream of the transcription initiation site is critical for the activation of the promoter by E2F3. In addition, expression of E2F3 positively correlates with the protein level of Aurora-A in human ovarian cancer examined. These results indicate for the first time that Aurora-A is transcriptionally regulated by E2F3 during the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…E2F3 is a member of cell cycle regulators and can directly bind to the CDE/CHR region of Aurora A promoters and induce Aurora A expression in the G 2 /M phase. 11 The function of E2F3 is regulated by p53 via the p21-CDK-Rb1 pathway. 24 To address whether E2F3 is involved in the upregulation of Aurora A in p53-knockdown cells, we performed a chromatin immunoprecipitation assay, analyzed the sequence of the Aurora A promoter, and found that the Aurora A promoter does contain an E2F binding site ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…E2F3 is a member of cell cycle regulators and can directly bind to the CDE/CHR region of Aurora A promoters and induce Aurora A expression in the G 2 /M phase. 11 The function of E2F3 is regulated by p53 via the p21-CDK-Rb1 pathway. 24 To address whether E2F3 is involved in the upregulation of Aurora A in p53-knockdown cells, we performed a chromatin immunoprecipitation assay, analyzed the sequence of the Aurora A promoter, and found that the Aurora A promoter does contain an E2F binding site ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such specificity indicates a delicate controlling process. Although the E2F site is known to be present in Aurora A promoter, 11 our studies provide insight into the link between p53 and E2F3 in the regulation of Aurora A transcription and fill an important knowledge gap. It is important to point out that that Aurora A also phosphorylates recombinant Rb1 in vitro (data not shown), which may further enhance the dissociation of E2F3 from Rb1.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…E2F3, a member of E2F family of transcription factors, binds specifically to RB1 protein, in a cell cycle-dependent manner, and plays a crucial role in the control of genes regulating S phase entry and DNA synthesis. 39,40 Amplification and overexpression of MDM2 on 12q15 were detected in 1 high-grade Ta case that presented with recurrences (Table 2). MDM2 overexpression has been shown to correlate with increasing stages and grades in urinary bladder cancer 41 and MDM2 amplification and TP53 mutation to be mutually exclusive 42 because MDM2 is a specific antagonist of TP53 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative fates subsequent to postmitotic defects induced by AAK and Aurora B kinase (ABK) inhibition are mediated in part by the p53 and p73 signaling pathways (35,36). In addition, Aurora A inhibition in a range of cell types has been shown to lead to a reduction in the rate of mitotic entry because of a late G 2 block in the cell cycle (37)(38)(39)(40). As is the case for traditional antimitotic agents, this complexity in the downstream cell biological consequences of Aurora A inhibition has led to challenges in the use of the mitotic index as a pharmcodynamic measurement in tumors.…”
Section: Introductionmentioning
confidence: 99%